Clinical Experience in a Community Setting During Pediatric Emergency Medicine Fellowship Training. Issue 10 (October 2020) - Marchese, Ronald F.; Gala, Payal K.; Seiden, Jeffrey A.; Scarfone, Richard; Belfer, Robert A.; Posner, Jill
Abstract : Objectives: The aim of this study is to explore current community emergency department (ED) experiences available to pediatric emergency medicine (PEM) trainees and estimate the proportion of graduates taking positions that involve working in a community ED setting. Methods: We conducted an e-mail–based survey among PEM fellowship directors and assistant directors. Results: There were 55 program director respondents (74% response rate). Thirty-one percent of the surveyed PEM fellowship programs provide training exposure to a community ED setting. Twenty-nine percent of the surveyed programs reported that 25% to 49% of graduating trainees accepted positions that involve working in a community hospital ED setting, 13% responded 50% to 74%, and 4% report 75% to 100% from 2012 to 2016. Conclusions: There is an overall paucity of a dedicated community rotation for PEM trainees, yet many graduates are seeking employment in community-based EDs. Because the need for community-based PEM physicians continues to rise and to adequately prepare the PEM workforce, PEM fellowship training should consider a curriculum that includes community-based ED clinical experiences.